Leitura e interpretação do gênero artigo de opinião: uma experiência reflexiva em ambiente socioeducativo : Fundação C.A.S.A - Manhani, Ana Beatriz [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Through the reading and knowledge, the human being is able to transform and modify the environment in which it is inserted, and live experiences through a dialogic reading and significant. The readings are worked with the aim of promoting a reflection and an interaction between the interlocutor, the reader and the text, making the significant texts and allowing the student the internal constitution of ethical and moral values, seeking to develop their awareness and critical spirit in relation to their rights and duties as citizens and helping them in their journey toward a new history of life in society. This research has as main objective will examine reader capacity and reflexive genre article of opinion and check dialogic, sociological and intertextually the work with the reading of examples of this kind in the classes of Portuguese language in a social and educational environment, in this case, the C.A.S.A Foundation (socioeductivo care center adolescentes). The development of a critical view of the student, their relationships with gifts speeches worked in the articles and the expansion of their communicative competence and consequently better exercise of citizenship, are the main issues discussed during the development of research. This research of the indicators proposed in the National Curricular Parameters for Portuguese Language, and is based on theories developed by authors who have proposed to study the text and genres thinking in Portuguese and reading instruction, among them we can mention, Elias; Koch (2006), Kleiman (2002), Leffa (1996), Marchuschi (2008), Solé (1998) and Todorov (1980). Other important references for the theoretical framework of this research are linked to Bakhtin Circle. From Bakhtin's theory, the teaching work stimulates the rebirth of participatory and critical student so that it can expose your opinion through speech and writing both in schools and in the...

Por meio da leitura e do conhecimento, o ser humano é capaz de se transformar e modificar o ambiente em que está inserido, além de vivenciar experiências através de uma leitura dialógica e significativa. As leituras são trabalhadas com o intuito de fomentar uma reflexão e uma interação entre o interlocutor, o leitor e o texto, tornando os textos significativos e possibilitando ao aluno interno a constituição de valores éticos e morais, buscando desenvolver sua consciência e espírito crítico em relação aos seus direitos e deveres enquanto cidadãos e auxiliando em seu caminho rumo a uma nova história de vida na sociedade. Esta pesquisa tem como objetivo principal analisara capacidade leitora e reflexiva do gênero artigo de opinião e verificar dialógica, sociológica e intertextualmente o trabalho com a leitura de exemplares desse gênero nas aulas de língua portuguesa em um ambiente socioeducativo, neste caso, a Fundação C.A.S.A (Centro de Atendimento Socioeducativo ao Adolescente). O desenvolvimento de uma visão crítica do aluno, suas relações com os discursos presentes nos artigos trabalhados e a ampliação de sua competência comunicativa e consequentemente um melhor exercício de cidadania, são os principais aspectos examinados durante o desenvolvimento desta. A presente pesquisa parte dos indicadores propostos nos Parâmetros Curriculares Nacionais de Língua Portuguesa, e está baseada em teorias desenvolvidas por autores que se propuseram a estudar os gêneros textuais e discursivos pensando no ensino de língua portuguesa e leitura, dentre eles, podemos citar, Elias; Koch (2006), Kleiman (2002), Leffa (1996), Marchuschi (2008), Solé (1998) e Todorov (1980). Outras importantes referências para o arcabouço teórico desta pesquisa estão ligadas ao Círculo de Bakhtin. A partir da teoria bakhtiniana, o trabalho docente estimula o renascer do aluno participativo...
Keywords: Leitura; Cidadania; Centros de reabilitação; Fundação Centro de Atendimento Socioeducativo ao Adolescente; Reading